Selling falsehoods? A cross-sectional study of Canadian naturopathy, homeopathy, chiropractic and acupuncture clinic website claims relating to allergy and asthma. Issue 12 (16th December 2016) - Murdoch, Blake; Carr, Stuart; Caulfield, Timothy
Abstract : Objective: To identify the frequency and qualitative characteristics of marketing claims made by Canadian chiropractors, naturopaths, homeopaths and acupuncturists relating to the diagnosis and treatment of allergy and asthma. Design: Cross-sectional study. Setting: Canada. Data set: 392 chiropractic, naturopathic, homeopathic and acupuncture clinic websites located in 10 of the largest metropolitan areas in Canada, as identified using 400 Google search results. Duplicates were not excluded from data analysis. Main outcome measures: Mention of allergy, sensitivity or asthma, claim of ability to diagnose allergy, sensitivity or asthma, claim of ability to treat allergy, sensitivity or asthma, and claim of allergy, sensitivity or asthma treatment efficacy. Tests and treatments promoted were noted as qualitative examples. Results: Naturopath clinic websites have the highest rates of advertising at least one of diagnosis, treatment or efficacy for allergy or sensitivity (85%) and asthma (64%), followed by acupuncturists (68% and 53%, respectively), homeopaths (60% and 54%) and chiropractors (33% and 38%). Search results from Vancouver, British Columbia were most likely to advertise at least one of diagnosis, treatment or efficacy for allergy or sensitivity (72.5%) and asthma (62.5%), and results from London, Ontario were least likely (50% and 40%, respectively). Of the interventions advertised, few are scientifically supported; the majority lack evidence of efficacy, and some are potentially harmful. Conclusions: The majority of alternative healthcare clinics studied advertised interventions for allergy and asthma. Many offerings are unproven. A policy response may be warranted in order to safeguard the public interest.